2014
DOI: 10.1093/jrr/rru005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term pathological and immunohistochemical features in the liver after intraoperative whole-liver irradiation in rats

Abstract: Radiation therapy (RT) has become particularly important recently for treatment of liver tumors, but there are few experimental investigations pertaining to radiation-induced liver injuries over long-term follow-up periods. Thus, the present study examined pathological liver features over a 10-month period using an intraoperative whole-liver irradiation model. Liver function tests were performed in blood samples, whereas cell death, cell proliferation, and fibrotic changes were evaluated pathologically in live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Criteria for diagnosing fibrosis as steatohepatitis in animals have not been determined. Therefore, many previous studies that have shown fibrosis in the liver in rodents as determined by Azan staining was assessed by comparison to control animals (Arima et al, 2014;Imaeda et al, 2014;Inami et al, 2015;Kolodziejczyk et al, 2015), which is consistent with this study. Therefore, we assessed the fibrosis in Mongolian gerbils fed a highfat/high-sucrose diet with β-carotene compared to those without β-carotene, as well as those fed a normal diet.…”
Section: Discussionsupporting
confidence: 88%
“…Criteria for diagnosing fibrosis as steatohepatitis in animals have not been determined. Therefore, many previous studies that have shown fibrosis in the liver in rodents as determined by Azan staining was assessed by comparison to control animals (Arima et al, 2014;Imaeda et al, 2014;Inami et al, 2015;Kolodziejczyk et al, 2015), which is consistent with this study. Therefore, we assessed the fibrosis in Mongolian gerbils fed a highfat/high-sucrose diet with β-carotene compared to those without β-carotene, as well as those fed a normal diet.…”
Section: Discussionsupporting
confidence: 88%
“…The oxidation of liver enzymes may underlie some radiation-induced alterations in hepatic function [2] . In addition to impaired liver function, increased apoptotic cell proportion, decreased hepatocyte number and fibrosis were also observed in irradiated livers [3] . Approximately 5 to 10 percent of the patients who receive a radiation dose in excess of 30Gy develop radiation-induced liver damage (RILD) [4] , [5] , [6] ; when the dose is increased to 43Gy, the prevalence of RILD increases to 50% [7] .…”
Section: Introductionmentioning
confidence: 99%
“…In a review of DC therapy, various reasons for the limitations of the treatment's efficacy were suggested, including inhibition of immune responses by regulatory T cells (Treg) and increase of the Treg number by transforming growth factor‐β (TGF‐β) . The elevated expression of TGF‐β1 was reported after whole or partial liver irradiation in in vivo studies . Therefore, irradiation to the normal liver using the TomoHelical mode might lead to increases in TGF‐β1 and Treg number, decreasing the efficacy of DC‐based vaccine therapy.…”
Section: Discussionmentioning
confidence: 99%
“…14 Palliative 3DCRT against the whole liver has also been used for multiple liver metastases in the past in Japan. Generally, the liver is sensitive to radiation and up to [30][31][32][33][34][35] Gy against the whole liver is considered to be the safe limit. 15 These doses are not high enough to obtain long-term control of liver metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation